Student Recreation Center, 1990 - Olson, Eric, photographer (Colorado State University. Libraries, 1990)
Exterior photo of the Student Recreation Center.
Not digitized by CSUL Digital Services.
Keywords: Student Recreation Center; athletics; exterior; recreation